2018
DOI: 10.1080/14786435.2018.1465239
|View full text |Cite
|
Sign up to set email alerts
|

Modelling study on the three-dimensional neutron depolarisation response of the evolving ferrite particle size distribution during the austenite–ferrite phase transformation in steels

Abstract: The magnetic configuration of a ferromagnetic system with mono-disperse and poly-disperse distribution of magnetic particles with inter-particle interactions has been computed. The analysis is general in nature and applies to all systems containing magnetically interacting particles in a non-magnetic matrix, but has been applied to steel microstructures, consisting of a paramagnetic austenite phase and a ferromagnetic ferrite phase, as formed during the austenite-to-ferrite phase transformation in low-alloyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…[18] The validity of the analysis was recently evaluated by simulated particle size distribution. [19] The influence of the particle size distribution was characterized in detail. The previous simulations confirm that Eq.…”
Section: Dnd Technique and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] The validity of the analysis was recently evaluated by simulated particle size distribution. [19] The influence of the particle size distribution was characterized in detail. The previous simulations confirm that Eq.…”
Section: Dnd Technique and Experimental Proceduresmentioning
confidence: 99%
“…In a recent study, we computationally analyzed the effect of the size distribution on the 3DND-derived microstructural parameters and found that the 3DND method, under certain conditions, may even yield information on the ferrite grain size distribution. [19] Therefore, the 3DND technique provides a powerful tool to simultaneously measure the ferrite fraction and the grain size within the bulk of steel samples. This technique has been used successfully to study austenite-to-ferrite [20] and austenite-to-pearlite [21] phase transformations in steels under isothermal conditions and during continuous cooling conditions.…”
Section: Introductionmentioning
confidence: 99%